The effect of articulate storyline-based interactive learning media to facilitate student learning independence - Wahyuni Nita; Ranny Meilisa; Imamudin; Roza Pebrianti; Hlaing Su Nandar (Researcher and Lecturer Society, 2023)
The problem in this study is whether there is an influence of interactive learning media-based articulate storyline to facilitate student learning self-reliance at SMKN 3 Serang City. This study aims to determine the effect of interactive learning media based on an articulate storyline to facilitate student learning self-reliance at SMKN 3 Serang City. The study was conducted in SMKN 3 Serang City, with samples of 35 students in Multimedia class XI. In this study, writers have used correlational quantitative methods, with data collection techniques of observation, questionnaires and documentation and based on the results of correlation analysis, using the T-test. Where the tcount is 40,282, and the table value is 2,035. Then tcount > ttable means that interactive learning media is influenced based on articulate storylines to facilitate student learning independence. The contribution of variable x to variable y is 98.01%, whereas 1.99% is affected by other factors, such as the internal being reviewed from physiological and psychological factors.